Mud shrimps of the genus Wolffogebia Sakai, 1982 (Decapoda: Gebiidea: Upogebiidae) with the description of a new species from the Cần Giớ Mangrove Biosphere Reserve, South Vietnam - Kolevatov, Vasily; Marin, Ivan (Zootaxa, 2022)
A new species of mud dwelling burrowing shrimp Wolffogebia cangioensis sp. nov. is described from the Soài Rạp River delta in the Cần Giớ Mangrove Biosphere Reserve, South Vietnam. The presence of Wolffogebia inermis Sakai, 1982 in the same area is also confirmed based on the freshly collected male specimen. Thorough morphological descriptions, genetic data (barcoding) and in situ ecological observations are presented for both species. A review of the previous records from Vietnam and Southeastern Asia as well as the taxonomic status of the genus Wolffogebia Sakai, 1982 within the family Upogebiidae are also discussed in the article. The key to all species of the genus is presented.